(untitled) (Riset Sains dan Teknologi Kelautan, 2026)
Eastern Indonesia has great potential for clean energy development, but still faces limitations in terms of electricity infrastructure and energy distribution in island and remote areas. Floating nuclear power plant (FNPP) are seen as an effective solution to meet these needs due to their flexible nature and ability to be located on outlying islands. This study presents a conceptual design for a Floating Nuclear Power Plant, focusing on a strategic location selection study in the waters of Eastern Indonesia. The research methodology includes secondary data analysis via satellite covering oceanographic aspects (waves, currents, sea depth), logistical accessibility, distance from population centres, potential connections to local electricity grids, as well as safety and environmental risk mitigation factors. By obtaining wave recurrence results, it is hoped that suitable locations for the placement of floating nuclear power plants can be identified, while also providing initial considerations for long-term energy planning in Eastern Indonesia. This research is expected to serve as a strategic reference in supporting sustainable energy provision and strengthening national energy security.